Review on resistive switching mechanisms of bio-organic thin film for non-volatile memory application - Cheong Kuan Yew (De Gruyter, 2021)
Bio-organic, as one of the sustainable and bioresorbable materials, has been used as an active thin film in producing resistive switching random access memory (RRAM) due to its specialized properties. This type of nonvolatile memory consists of a simple unit structure with the processed and solidified bio-organic-based thin film sandwiched between two electrodes. Its memory characteristics are significantly affected by the resistive-switching mechanism. However, to date, the reported mechanisms are very diverse and scattered, and to our best knowledge, there is no literature that reviewed comprehensively the mechanisms of resistive switching in bio-organic-based thin films. Therefore, the objective of this article is to critically analyze data related to the mechanisms of the bio-organic-based RRAM since it was first reported. Based on the pool of literature, three types of mechanisms are categorized, namely electronic, electrochemical, and thermochemical, and the naming is well justified based on the principle of operation. The determining factors and roles of bio-organic material and the two electrodes in governing the three mechanisms have been analyzed, reviewed, discussed, and compared.